Galen - Nutton, Vivian, author.
1 online resource.
Keywords: "This volume offers a comprehensive biography of the Roman physician Galen, and explores his activities and ideas as a doctor and intellectual, as well as his reception in later centuries. Nutton's wide-ranging study surveys Galen's early life and medical education, as well as his later career in Rome and his role as court physician for over forty years. It examines Galen's philosophical approach to medicine and the body, his practices of prognosis and dissection, and his ideas about preventative medicine and drugs. A final chapter explores the continuing impact of Galen's work in the centuries after his death, from his pre-eminence in Islamic medicine to his resurgence in Western medicine in the Renaissance, and his continuing impact through to the 19th century even after the discoveries of Vesalius and Harvey. Galen is the definitive biography this fascinating figure, written by the preeminent Galen scholar, and offers an invaluable resource for anyone interested in Galen and his work, and the history of medicine more broadly"--